Subclinical leaflet thrombosis after transcatheter aortic valve implantation is associated with silent brain injury on brain magnetic resonance imaging. (28th September 2022) - Apor, Astrid; Bartykowszki, Andrea; Szilveszter, Bálint; Varga, Andrea; Suhai, Ferenc I; Manouras, Aristomenis; Molnár, Levente; Jermendy, Ádám L; Panajotu, Alexisz; Turáni, Mirjam Franciska; Papp, Roland; Karády, Júlia; et al.
Abstract: Aims: Whether hypoattenuated leaflet thickening (HALT) following transcatheter aortic valve implantation (TAVI) carries a risk of subclinical brain injury (SBI) is unknown. We investigated whether HALT is associated with SBI detected on magnetic resonance imaging (MRI), and whether post-TAVI SBI impacts the patients' cognition and outcome. Methods and results: We prospectively enrolled 153 patients (age: 78.1 ± 6.3 years; female 44%) who underwent TAVI. Brain MRI was performed shortly post-TAVI and 6 months later to assess the occurrence of acute silent cerebral ischaemic lesions (SCIL) and chronic white matter hyperintensities (WMH). HALT was screened by cardiac computed tomography (CT) angiography (CTA) 6 months post-TAVI. Neurocognitive evaluation was performed before, shortly after and 6 months following TAVI. At 6 months, 115 patients had diagnostic CTA and 10 had HALT. HALT status, baseline, and follow-up MRIs were available in 91 cases. At 6 months, new SCIL was evident in 16%, new WMH in 66%. New WMH was more frequent (100 vs. 62%; P = 0.047) with higher median volume (319 vs. 50 mm3; P = 0.039) among HALT-patients. In uni- and multivariate analysis, HALT was associated with new WMH volume (beta: 0.72; 95%CI: 0.2–1.39; P = 0.009). The patients' cognitive trajectory from pre-TAVI to 6 months showed significant association with the 6-month SCIL volume (beta: −4.69; 95%CI: −9.13 to 0.27; P = 0.038), but was not related to the presence or volume of new WMH. During a 3.1-year follow-up, neither HALT [hazard ratio (HR): 0.86; 95%CI: 0.202–3.687; P = 0.84], nor the related WMH burden (HR: 1.09; 95%CI: 0.701–1.680; P = 0.71) was related with increased mortality. Conclusions: At 6 months post-TAVI, HALT was linked with greater WMH burden, but did not carry an increased risk of cognitive decline or mortality over a 3.1-year follow-up (NCT02826200). Graphical Abstract: Graphical Abstract